Social support by communities for older adults in Malaysia - Marzuki, Abdul Aziz; Nor, Nik Norliati Fitri Md; Rashid, Siti Masayu Rosliah Abdul; Ghazali, Suriati (Nurture, 2023)
Purpose: Positive developments in the socioeconomic field have led to a reduction in mortality and fertility rates and an increase in the lifespan of individuals. This has reduced the young population and increased the old population. Senior citizens are being neglected, and loneliness is getting worse every day because of these circumstances. Therefore, in order to address the problem, there is a pressing urgency to identify how to provide support to older adults so that they can continue their daily lives easily without any problems or obstacles that can limit their activities. Social support refers to support in terms of emotions, friends, information, care, and management. Design/Methodology/Approach: A total of 397 questionnaire forms were distributed by purposive sampling to older adults aged 60 years and above in the Perak state and analyzed using descriptive statistical tests to obtain frequency, mean, and percentages for Social Science (SPSS) software. Findings: The results of the study showed that the older adults majorly agreed with the form of social support which was provided by the community. However, based on the social support, older adults are more likely to feel accompanied by neighbours, friends, or individuals. The study discovered that older persons prefer to be to be actively involved in the society, since this also enables them to deal with severe difficulties, circumstances, and fears. This preference is demonstrated by the total degree of social assistance provided and the daily activities of the older adults. Conclusion: The availability of social support indirectly contributes to the well-being of older adults by addressing the neglect and loneliness they may face, enabling them to maintain active and fulfilling lives. It promotes active aging by fostering social connections, enhancing mental and emotional health, and empowering older individuals to participate fully in society. Contribution to Literature Review: Social support, encompassing community support, emotional support, peer support, and information support, contributes significantly to the well-being of older adults. These forms of support help address the issues of neglect and loneliness faced by older adults, enabling them to actively age and lead fulfilling lives. The literature highlights the importance of social support systems in promoting the well-being of older adults and emphasizes the need for comprehensive support from various parties to meet the growing needs of the aging population. The literature on social support for older adults has important policy implications for promoting their well-being and addressing the challenges they face such as strengthening community support systems and encouraging peer support programs.